The adenosinergic signaling in the pathogenesis and treatment of multiple sclerosis - Duarte-Silva, Eduardo; Ulrich, Henning; Oliveira-Giacomelli, Ágatha; Hartung, Hans-Peter; Meuth, Sven G.; Peixoto, Christina Alves (Frontiers in Immunology, 2022)
Multiple sclerosis (MS) is a highly disabling, progressive neurodegenerative disease with no curative treatment available. Although significant progress has been made in understanding how MS develops, there remain aspects of disease pathogenesis that are yet to be fully elucidated. In this regard, studies have shown that dysfunctional adenosinergic signaling plays a pivotal role, as patients with MS have altered levels adenosine (ADO), adenosine receptors and proteins involved in the generation and termination of ADO signaling, such as CD39 and adenosine deaminase (ADA). We have therefore performed a literature review regarding the involvement of the adenosinergic system in the development of MS and propose mechanisms by which the modulation of this system can support drug development and repurposing.